The Blackness in Almutanabbi’s Poetry - Al-Muhaimid, May Bint Ibrahim (Arab Journal for Sciences and Research Publishing, 2018)
This study examines the phenomenon of blackness، its causes، and its linguistic connotations in Almutanabbi's poetry.The research follows the semiotic approach to poetic discourse analysis.Results:1- In Almutanabbi’s poetry، the meanings of blackness vary from one era to another.2- Almutanabbi made the black color a symbol of different meanings.
Keywords: Blackness in Al-Mutanabbi's Poetry; A Semiotic Study